Financialization of the environment: responses presented at COP-26 to slow climate change - Fernandes, Carolina (Geografares, 2024)
This article discusses the trend of financialization of the environment that emerged along with the neoliberal State. States, although central actors, are increasingly losing their central role in the development of public policies for environmental protection aimed at mitigations the effects of climate change. The first part of the article has a brief theoretical debate regarding the financialization of the environment. In the second part, we analyze how this trend has materialized. To this end, we analyze the results of the last Conference of the Parties (COP-26), which took place in Glasgow, UK, in November 2021, namely: Glasgow Climate Pact, Glasgow Leaders Declaration on Forests and Land Use and LEAF Coalition.